The Role Of E-Commerce In Community Economic Resurgence Post Covid-19 - Permatasari, Oktaviani (The International Journal of Business Review (The Jobs Review), 2021)
Abstract. The COVID-19 epidemic has had a severe impact on the economic sector of the community. The implementation of PSBB and WFH makes it difficult for people to fulfill their daily needs, however technological developments have created new opportunities in business, one of which is E-Commerce, which is used by online business people.The purpose of this research is to what extent E-Commerce is in the revival of the community economy after COVID-19. The method used in this study uses the System Literature Review (SLR), by examining several sources used as material in finding and obtaining literature including books, articles, electronic media and the web.Based on the results of data analysis, E-Commerce is one of the sectors driving the Indonesian economy after COVID-19, but it must be accompanied by high optimism for all business actors, stakeholders and society so that national economic conditions can rise after COVID -19.Keyword. e-commerce; community economic resurgence; post-COVID-19